Contextualising Computational Thinking: A Case Study in Remote Rural Sarawak Borneo - Nur Hasheena, Anuar; Fitri Suraya, Mohamad; Jacey Lynn, Minoi (International Journal of Learning, Teaching and Educational Research, 2020)
The paper describes an exploratory case study on novice indigenous children’s learning characteristics as they learn Computational thinking (CT) competencies, such as abstraction, decomposition, and algorithmic thinking. It employs a quasi-experimental research design with pre-test and post-test instruments. Twenty-two children of an underprivileged Penan community living in a remote village in Sarawak Borneo participated. Through the study, they learned Computational thinking skills using localised instructional strategies, with Scratch™ as their tool to programme. The study used observational field notes, comprehension checks, and participants’ learning products as primary data sources. Findings showed that indigenous children’s learning characteristics were primarily ‘learning-by-making’, collaborative, highly motivated, playful, curious, and imaginative while they attempted to learn Computational thinking. The intervention (treatment) group performed marginally better than the control group in the pre-test and were substantially better in the post-test performance. Findings illustrate a direction in which novice indigenous children could learn and be informed about Computational thinking practices and skills through a mix of game-based learning, collaborative learning, problem-based learning, and project-based learning. Findings also revealed how participants appeared to have gained self-confidence, illustrated creativity on task and were self-critical throughout their participation in the study.